Transcriptome comparative analysis of immune tissues from asymptomatic and diseased Epinephelus moara naturally infected with nervous necrosis virus. Issue 93 (October 2019) - Wang, Linna; Tian, Yongsheng; Cheng, Meiling; Li, Zhentong; Li, Shangyong; Wu, Yuping; Zhang, Jingjing; Ma, Wenhui; Li, Wensheng; Pang, Zunfang; Zhai, Jieming
Abstract: Epinephelus moara is an economically important fish in Southeast Asian countries but is suffering from nervous necrosis virus (NNV) infection. A deeper understanding of the host-NNV interaction mechanisms makes sense for disease control, however, at present, the pathogenesis of natural NNV infection and the resistance mechanism in host remains poorly understood. In this study, asymptomatic and diseased E. moara with clinical symptoms of viral nervous necrosis (VNN) from a grouper farm were both detected with a positive RT-PCR signal of NNV, then transcriptome sequencing of their immune tissues (liver, spleen and kidney) were performed for comparation analysis. The de novo assemblies yielded 53, 789 unigenes which had a length varied from 201 to 19, 675 bp and a N50 length of 2115 bp, and 29, 451 unigenes were functionally annotated, with 83, 250 and 5632 unigenes being differentially expressed in liver, spleen and kidney respectively. KEGG pathway enrichment analysis of the DEGs showed many DEGs were enriched in immune related pathways. Although the expression of class I major histocompatibility complex (MHC) was significantly higher in three immune tissues of the diseased grouper, many immune related genes, including humoral immune molecules (such as antibodies), the cellular mediated cytotoxic molecules (such as perforin) and some adhesion related genes were down regulated in the diseased grouper. Our results provided many unigenes that might play important roles in NNV resistance for further research. Furthermore, a total of 8666 unigenes containing 11, 623 simple sequence repeats (SSRs) were identified, which provided useful information for screening molecular markers associated with NNV resistance in E. moara . Highlights: Both asymptomatic and diseased grouper were naturally infected with NNV. First report of transcriptome analysis of E. moara liver, spleen and kidney tissues. This study revealed a comprehensive view of NNV persistent infection. This study provided many unigenes associated with NNV resistance in E. moara. This study provided many SSRs for screening molecular markers.